Incarcerated Sex Offenders in Rehabilitation Account for their Offending. Issue 1 (21st June 2016) - Geiger, Brenda; Fischer, Michael
Abstract: This research examines the accounts of 10 out of 22 incarcerated sex offenders undergoing therapy in one of the prison‐based sex‐offender rehabilitation units in Israel and their ability to renegotiate reality to reject stigmatisation and maintain a favourable identity. The research participants had been convicted either of child molestation or of date/statutory rape against an acquaintance. This differentiation was maintained when analysing the individual interviews conducted in prison. Prior to the provision of accounts, to establish the soundness of their character, the interviewees resituated themselves within a normative background in terms of setting, routine activities, and interactions preceding and following the offence. Offenders convicted of child molestation attributed their behaviour to a sudden unpredictable shift in the setting and interactions with the child that resulted in an erection and consequent impulsive sexual behaviour of which they could not be held responsible. Offenders convicted of date/statutory rape admitted responsibility for their action, yet minimised its harm by attributing it to the dynamic chain of interactions with the victim whose behaviour had deviated from the 'good' girl or 'macho' man on a date and thus had precipitated the act. Rather than discounting sex offenders' accounts as cognitive distortions of a sick mind, prevention and education programme are to rely on such accounts to increase youth and young adult awareness to traditional gender‐role schemata and dating scripts espoused by Israeli macho men that facilitate date rape and to the dynamics of interactional and situational factors placing young children at risk of sexual victimisation. Copyright © 2016 John Wiley & Sons, Ltd.